Pengaruh Periklanan Tokopedia Terhadap Keputusan Pembelian Pada Mahasiswa Mercu Buana Jakarta - Ogrivia ratih puspa ningrum (Universitas Mercu Buana, 2020)
Internet users are increasing every year and the current pandemic conditions indicate an increase in online shopping transactions. Indonesian consumers remain the most active online shoppers, and around 14% of them shop online using smartphones, tablets or other mobile devices. One of the e-commerce is Tokopedia, in increasing its transactions, it carries out advertising activities with the aim that people are interested in opening the Tokopedia application and making transactions on the application. Waktu Indonesia Belanja program using the K-POP model that is currently in demand by the public has become an advertising program carried out by Tokopedia.The approach to Tokopedia's advertising research is to use the Heuristic Systematic Model for purchasing decisions. This study aims to determine the effect of Tokopedia advertising on purchasing decisions for students at Mercu Buana University Jakarta using the Heuristic Systematic Model.Data analysis in this study was carried out by distributing questionnaires to 384 respondents who became the sample of this study where the sampling technique was proportional stratified random sampling, then further analysis was carried out with multiple linear regression models using the SPSS program.The results showed that there was a positive and significant influence between advertising processing carried out heuristically on purchasing decisions, as well as advertising processing carried out systematically which showed a positive and significant influence on purchasing decisions. The magnitude of the effect of systematic processing on purchasing decisions is greater than that of heuristic processing. Simultaneously, advertising processing which is carried out heuristically and systematically shows a positive and significant influence on purchasing decisions. Keywords: Heuristic and Systematic Models, Purchase Decisions, Advertising, Market Places, E-Commerce